2000
DOI: 10.1084/jem.192.11.1677
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Form of B Cell Maturation Antigen, a Receptor for the Tumor Necrosis Factor Family Member April, Inhibits Tumor Cell Growth

Abstract: A proliferation-inducing ligand (APRIL) is a ligand of the tumor necrosis factor (TNF) family that stimulates tumor cell growth in vitro and in vivo. Expression of APRIL is highly upregulated in many tumors including colon and prostate carcinomas. Here we identify B cell maturation antigen (BCMA) and transmembrane activator and calcium modulator and cyclophilin ligand (CAML) interactor (TACI), two predicted members of the TNF receptor family, as receptors for APRIL. APRIL binds BCMA with higher affinity than T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
204
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(215 citation statements)
references
References 17 publications
9
204
0
2
Order By: Relevance
“…Indeed, PRIL was also shown to provide a proliferative/survival signal to solid tumor cells. Although only modestly detectable in vitro (Hahne et al, 1998;Roth et al, 2001), this activity has been observed significantly in vivo by overexpressing APRIL in tumor cells (Hahne et al, 1998) or by blocking endogenous PRIL (Rennert et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PRIL was also shown to provide a proliferative/survival signal to solid tumor cells. Although only modestly detectable in vitro (Hahne et al, 1998;Roth et al, 2001), this activity has been observed significantly in vivo by overexpressing APRIL in tumor cells (Hahne et al, 1998) or by blocking endogenous PRIL (Rennert et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[6][7][8][9][10] In BLyS deficient mice, the number of B cells, serum IgG and IgM levels were decreased, and B cell development was blocked at the transitional T1 stage. 11 BLyS and a proliferation-inducing ligand (APRIL) bind to B cell maturation antigen (BCMA) and transmembrane activator and CAML-interactor (TACI), 4,12,13 which belong to the tumor necrosis factor receptor superfamily and are mainly expressed in B cells. [14][15][16][17] The intracellular domains of BCMA and TACI associate with TNFreceptor-associated factors (TRAFs), leading to activation of NF-kB.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, APRIL interacts with proteoglycans, which are structurally unrelated to TNF receptors, and are likely to be the initially unidentified APRILspecific binding partner that was predicted to exist several years ago (K Ingold et al, unpublished; [6]). This interaction involves acidic sulfated glycosaminoglycan (GAG) sidechains of proteoglycans and basic amino acid residues, which are present in APRIL, but not in BAFF, and is independent from the interaction site for TACI and BCMA (K Ingold et al, unpublished; Figure 2).…”
Section: The Interactions Of Baff and April With Their Receptors And mentioning
confidence: 99%